Personality and weight management in adults with type 2 diabetes: A systematic review - Geerling, Ralph; Kothe, Emily J.; Anglim, Jeromy; Emerson, Catherine; Holmes-Truscott, Elizabeth; Speight, Jane (Frontiers in Clinical Diabetes and Healthcare, 2022)
Aims Managing weight in the context of type 2 diabetes presents unique hormonal, medicinal, behavioural and psychological challenges. The relationship between weight management and personality has previously been reviewed for general and cardiovascular disease populations but is less well understood in diabetes. This systematic review investigated the relationship between personality constructs and weight management outcomes and behaviours among adults with type 2 diabetes. Methods Medline, PubMed, Embase, PsycINFO and SPORTDiscus databases were searched to July 2021. Eligibility: empirical quantitative studies; English language; adults with type 2 diabetes; investigation of personality-weight management association. Search terms included variants of: diabetes, physical activity, diet, body mass index (BMI), adiposity, personality constructs and validated scales. A narrative synthesis, with quality assessment, was conducted. Results Seventeen studies were identified: nine cross-sectional, six cohort and two randomised controlled trials (N=6,672 participants, range: 30-1,553). Three studies had a low risk of bias. Personality measurement varied. The Big Five and Type D personality constructs were the most common measures. Higher emotional instability (neuroticism, negative affect, anxiety, unmitigated communion and external locus of control) was negatively associated with healthy diet and physical activity, and positively associated with BMI. Conscientiousness had positive associations with healthy diet and physical activity and negative associations with BMI and anthropometric indices. Conclusions Among adults with type 2 diabetes, evidence exists of a relationship between weight management and personality, specifically, negative emotionality and conscientiousness. Consideration of personality may be important for optimising weight management and further research is warranted. Systematic review registration www.crd.york.ac.uk/prospero/, identifier CRD42019111002.